Retrospective analysis of risk factors and gaps in prevention strategies for mother-to-child HIV transmission in Rio de Janeiro, Brazil - Kathryn Lynn Lovero; Thais Raquelly Dourado de Oliveira; Estela Magalhães Cosme; Natália Beatriz Cabrera; Mariana Fernandes Guimarães; Juliana Gregório de Avelar; Giovanna Rodrigues Teixeira de Oliveira; Camila de Morais Salviato; Guillermo Douglass-Jaimes; Maria Leticia Santos Cruz; Esaú Custódio João; Ana Cláudia Mamede Wiering de Barros; et al. (BMC, 2018)
Abstract Background Despite great progress made in methods to prevent mother-to-child transmission of HIV (MTCT), delivery and uptake of these measures remains a challenge in many countries. Although the Brazilian Ministry of Health aimed to eliminate MTCT by 2015, infection still occured in 15-24% of infants born to HIV-infected mothers. We sought to identify remaining factors that constrain MTCT elimination. Methods We conducted a retrospective, matched case-control study by reviewing hospital charts of infants born to HIV-infected mothers between 1997 and 2014 at three MTCT reference hospitals in the Rio de Janeiro metropolitan area. Cases were defined as HIV-exposed children with two positive HIV tests before 18 months of age; controls were defined as HIV-exposed children with two negative HIV tests before 18 months of age. We performed bivariate and MTCT cascade analyses to identify risk factors for MTCT and gaps in prevention services. Results We included 435 infants and their mothers (145 cases, 290 controls). Bivariate analyses of MTCT preventative care (PMTCT) indicated that cases were less likely to complete all individual measures in the antenatal, delivery, and postnatal period (p < 0.05). Assessing completion of the PMTCT cascade, the sequential steps of PMTCT interventions, we found inadequate retention in care among both cases and controls, and cases were significantly less likely than controls to continue receiving care throughout the cascade (p < 0.05). Motives for incompletion of PMTCT measures included infrastructural issues, such as HIV test results not being returned, but were most often due to lack of care-seeking. Over the course of the study period, PMTCT completion improved, although it remained below the 95% target for antenatal care, HIV testing, and antenatal ART set by the WHO. Adding concern, evaluation of co-infections indicated that case infants were also more likely to have congenital syphilis (OR: 4.29; 95% CI: 1.66 to 11.11). Conclusions While PMTCT coverage has improved over the years, completion of services remains insufficient. Along with interventions to promote care-seeking behaviour, increased infrastructural support for PMTCT services is needed to meet the HIV MTCT elimination goal in Brazil as well as address rising national rates of congenital syphilis.